A multi-stakeholder multicriteria decision analysis for implantable medical devices assessment in China - Xu, Yizhou; Wan, Junjie; Wan, Bin; Ding, Haixia (Frontiers in Health Services, 2025)
ObjectivesThis study aims to develop a standardized multicriteria decision analysis (MCDA) framework tailored for implantable medical devices in China, addressing the challenges of inconsistent evaluation processes under China's evolving healthcare financing policies.MethodsA mixed-methods design combining a discrete choice experiment (DCE) and MCDA was employed. Six criteria (clinical effectiveness, clinical safety, innovation, disease severity, implementation capacity, and cost) were identified through literature reviews and expert consultations. A DCE survey with 540 multi-stakeholder participants (decision-makers, HTA experts, clinicians, hospital administrators, and citizens) was conducted to derive criterion weights using mixed logit models. The framework was validated through a real-world case study assessing endoscopic linear staplers.ResultsClinical safety (35.45%) and cost (27.94%) emerged as the most critical criteria, followed by implementation capacity (16.56%) and clinical effectiveness (15.07%). Innovation (2.54%) and disease severity (2.44%) received minimal weight. The MCDA application demonstrated high inter-rater consistency (CV < 0.25).ConclusionsThis study proposes a transparent, stakeholder-driven framework for evaluating implantable medical devices, specifically designed to support China's healthcare policies. The framework ensures that healthcare decisions are grounded in clinical effectiveness, safety, and long-term economic viability.